Spiritual healing scientific and religious perspectives - Watts, Fraser N. (Cambridge ; New York : Cambridge University Press, 2011)
"There has recently been much interest in the relationship between science and religion, and how they combine to give us a 'binocular' perspective on things. One important phenomenon which has been neglected in recent work is the concept of spiritual healing. This edited collection explores a variety of approaches to spiritual healing from different religious points of view, identifying both what it is and how it works. The authors also explore the biological and psychological processes, open to scientific enquiry, through which healing may be mediated. As such, this book indicates the central proposition that religious and scientific perspectives answer different questions about healing, and there is not necessarily any conflict between them"--
Machine generated contents note: List of contributors; Preface; 1. Conceptual issues in spiritual healing Fraser Watts; 2. The historical Jesus and healing: Jesus' miracles in psycho-social context Justin Meggitt; 3. The theology of spiritual healing Philip Clayton; 4. Healing the spirit: mystical Judaism, religious texts and medicine Simon Dein; 5. Conceptualisations of spiritual healing: Christian and secular Charles Bourne and Fraser Watts; 6. The psychodynamics of spiritual healing and the power of mother kissing it better Bruce Kinsey; 7. Spiritual healing in the context of the human need for safeness, connectedness and warmth: a biopsychosocial approach Paul Gilbert; 8. Modeling the biomedical role of spirituality through breast cancer research Michael Boivin and Burton Webb; 9. Spirituality and health: assessing the evidence Marilyn Schlitz; 10. Relating spiritual healing and science: some critical reflections David Leech; 11. Concluding integration Fraser Watts.
Includes bibliographical references (p. 181-203) and index.
Description based on print version record.
Keywords: Spiritual healing; Healing -- Religious aspects -- Christianity; Medicine -- Religious aspects -- Christianity; Healing -- Religious aspects; Medicine -- Religious aspects; Religion and science; Electronic books; RELIGION / Reference